Breaking the Cycle—Rethinking Substance Use Care in Nepal - Dhakal, Aashish; Maharjan, Shreejana; Dahal, Prerana (Nepal Journal of Neuroscience, 2025)
Substance use disorder (SUD) remains a deeply entrenched public health challenge in Nepal. Despite advances in understanding addiction as a chronic medical condition, the national response continues to be shaped by cultural taboo, inadequate treatment models, and insufficient pathways for societal reintegration. This editorial argues that unless Nepal transitions from punitive and institutional approaches to a rights‑based, evidence‑driven model, the cycle of relapse, stigma, and marginalization will persist.